SecCloud: Bridging Secure Storage and Computation in Cloud - Lifei Wei; Haojin Zhu; Zhenfu Cao; Weiwei Jia; Vasilakos, A V (2010 IEEE 30th International Conference on Distributed Computing Systems Workshops, 2010)
Cloud computing becomes a hot research topic in the recent years. In the cloud computing, software applications and databases are moved to the centralized large data centers, which is called cloud. In the cloud, due to lack of physical possession of the data and the machine, the data and computation may not be well managed and fully trusted by cloud users. Existing work on cloud security mainly focuses on cloud storage without taking computation security into consideration. In this paper, we propose SecCloud, a novel auditing scheme to secure cloud computing based on probabilistic sampling technique as well as designated verifier technique, which aims to consider secure data storage, computation and privacy preserving together. We also discuss how to optimize sampling size to minimize the auditing cost. Detailed analysis and simulations have demonstrated the effectiveness and efficiency of the proposed scheme.